Science Diplomacy and South-South Cooperation for Emergency Response: The Case of COVID-19 pandemic in Latin America - Luisa Fernanda Echeverria; Karina Elizabeth Aquino Valle; Claudia Natalie Widmaier Muller (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2020)
AbstractLatin America is a highly culturally and socioeconomically diverse region and it has a long story dealing with a weak, inequitable, inefficient and fragmented health system. The world faces a global health crisis without precedent, where global action and solidarity are crucial. This article highlights the importance of South-South cooperation actions based on science diplomacy, from countries in Latin America, for health-related emergencies, such as the COVID-19 pandemic. As the qualitative research, this article will first present the concepts of science diplomacy and South-South Cooperation; secondly it will describe how these two concepts can contribute to emergencies associated with health related situations. Then, this article will review initiatives from Latin America to address the current pandemic. Finally, the general conclusions of the article will be presented. The management of the pandemic requires the best public health strategies contributing to its containment, but also an integrated approach using the transfer of good practices between the Global South, creating a network of scientists and diplomats working together to find possible solutions to the disease. South-South cooperation in Latin America occurs mainly bilaterally, especially with other countries in the Global South. Latin America has to work as a region to generate more spaces for collaboration, addressed by governments to achieve universal health.